The effect of chronic ethanol administration on total number of pyramidal cells in CA 1 and CA3 of hippocampus and spatial working memory in adolescent rats (Rattus norvegicus) - Muh. Ihwan Nurwanto Soejono Aswin Mustofa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Adolescent brain may be more susceptible to damage by ethanol. Chronic ethanol administration may cause morphological changes in the hippocampus, followed by deficit in the hippocampal function, including the impairment of memory.Objective: The aim of this study were to investigate the changes in the total number of pyramidal cells in CA 1 and CA3 of hippocampus, and the relationship between these changes with spatial working memory of rats after chronic ethanol administration at adolescent age.Methods: Twenty five adolescent (30 days of agel male rats (Rattus norvegicusl were classified randomly into 5 groups, that is, namely control without treatment (C1 I, control with treatment (C21, treatment 1(11 I, treatment 2 (T2), and treatment 3 (T31 groups. Each group consisted of 5 rats. C2 group was given physiological saline, while 11, T2, and T3 groups were given ethanol at various doses of 1, 2, and 3 gl kgBW/day, repectively, for 30 days by intraperitoneal injection. After chronic ethanol administration, the spatial working memory of 5 groups were tested using 8 arms radial maze for 12 days. At the end of the experiment, the rats were sacrified and the brains were taken out for histological examination, by paraffin method and Cresyl violet staining.Result: Chronic ethanol administration on adolescent rats caused a decrease in spatial working memory (especially in group T31 (p < 0.051. The total number of pyramidal cells in CA 1 of group T3 was fewer than those of control groups (p < 0.05), but the total numbers of pyramidal cells in CA3 of treatment groups were not different with those of control groups (p > 0.051. Analysis with product moment correlation test showed that there was a positive correlation between the total number of pyramidal cells in CA 1 of hippocampus with spatial working memory of the rats after chronic ethanol administration at adolescent age (p < 0.051.Conclusion: Chronic ethanol administration on adolescent rats caused a decrease in the spatial working memory and the number of pyramidal cells in CA 1 of hippocampus. There was a positive correlation between the number of pyramidal cells in CA 1 and spatial working memory of the rats after chronic ethanol administration at adolescent age.Key words: ethanol - pyramidal cells - spatial working memory - adolescent